(3NGOe GdQhVI hGdQGaYis - (3GdRQcTj , eMeO Hf HgGOQ Hf YHO Gddg, HOQ GdOjf CHh YHO Gddg,J (B794 (3g` s
(3ChdgG (B:s
(3Ce HYO agPG cJGH jMJGL Edi GdYeQGdWhjd hGdage GdLdjd s
(3BNQgG (B:s
(3hjdRe GdbGVi CHG GdWjH Cfg dGjHjM Medg dPi GdMOK GdOGFe eY GdhVhA dCfg dGjQaY GdMOK hgh HYjO Je GdLRA hjJdhg aj GdLRA GdPj jdjg GdHGH GdQGHY aj GdZSd s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs